Transcatheter Aortic Valve Replacement With Self‐Expandable Supra‐Annular Valves for Degenerated Surgical Bioprostheses: Insights From Transcatheter Valve Therapy Registry - Luis Augusto P. Dallan (Wiley, 2021)
Background Transcatheter aortic valve replacement with supra‐annular transcatheter heart valves has been adopted in patients with degenerated surgical aortic valves. The next generation self‐expanding Evolut PRO valve has not been evaluated in patients with surgical valve failure. Methods and Results Patients undergoing transcatheter aortic valve replacement in degenerated surgical aortic valve procedures using the Evolut R or Evolut PRO transcatheter heart valves in the Society of Thoracic Surgeons and American College of Cardiology Transcatheter Valve Therapy Registry between April 2015 and June 2019 were evaluated. Transcatheter valve performance was evaluated by clinical site echocardiography. In‐hospital, 30‐day, and 1‐year clinical outcomes were based on the Society of Thoracic Surgeons‐American College of Cardiology‐Transcatheter Valve Therapy registry definitions. Transcatheter aortic valve replacement in degenerated surgical aortic valve was performed in 5897 patients (5061 [85.8%] patients received the Evolut R valve and 836 [14.2%] received the Evolut PRO valve). Thirty‐day transcatheter heart valves hemodynamic performance was excellent in both groups (mean gradient: Evolut PRO: 13.8±7.5 mm Hg; Evolut R: 14.5±8.1 mm Hg), while paravalvular regurgitation was significantly different between valve types (P=0.02). Clinical events were low at 30 days (Evolut PRO: for the all‐cause mortality, 2.8%, any stroke was 1.8%, new pacemaker implantation, 3.0%: Evolut R:all‐cause mortality, 2.5%, any stroke was 2.2%, new pacemaker implantation, 5.3%) and 1 year (Evolut PRO: all‐cause mortality, 9.2%; any stroke, 3.1%; Evolut R: all‐cause mortality, 9.8%; any stroke, 2.9%). Conclusions Transcatheter aortic valve replacement in degenerated surgical aortic valve with self‐expandable supra‐annular transcatheter heart valves is associated with excellent clinical outcomes and valve hemodynamics. Additional reductions in residual paravalvular regurgitation were obtained with the next generation Evolut PRO.